History, theory and practice of philosophy for children: international perspectives - Naji, Saeed (Taylor & Francis, 2017)
This book on Philosophy for Children (P4C) is a compilation of articles written by its founders and the movement‘s leaders worldwide. These articles have been prepared in the dialogue and interview format. Part I explains the genesis of the movement, its philosophical and theoretical foundations. Part II examines the specialized uses of philosophical dialogues in teaching philosophy, morality, ethics and sciences. Part III examines the theoretical concerns such as the aims of the method in regards to the search for truth or sense of meaning, or the debate on the novel or short stories and its characteristics. Part IV explains the practices of P4C worldwide and the issue of cultural differences, the ways of the community of inquiry and the necessary adaptation to suit local concerns. The book concludes with a notable review of the progress of P4C, the obstacles, and its international spread to over 60 countries. These penetrating insights make the book an incredibly rich resource for anyone interested in or involved with implementing a P4C programme.